Calcium and pH interaction limits bloom formation and expansion of a nuisance microalga. Issue 9 (30th July 2021) - Gollnisch, Raphael; Alling, Teodor; Stockenreiter, Maria; Ahrén, Dag; Grabowska, Magdalena; Rengefors, Karin
Abstract: Microalgal range expansions are increasing in frequency and magnitude but generally remain unnoticed until mass development occurs. Gonyostomum semen is a freshwater raphidophyte that causes nuisance blooms in lakes and has recently expanded its distribution across Europe. G. semen was considered to mainly occur in humic lakes in the boreal region but is now found in high density also in other freshwater habitats on a larger geographic scale with growing incidence. In this study, we focused on which environmental factors limit its expansion. Our hypothesis was that G. semen occurs in many different lake types, except for high alkalinity lakes, in which high pH in combination with high calcium concentration would inhibit its growth. Results from our field study illustrate the environmental heterogeneity of G. semen bloom sites across Europe and the United States. Nevertheless, none of these sites combined high pH and high calcium concentration. In a mesocosm study, as well as a laboratory experiment, we further demonstrated that growth of G. semen is inhibited in conditions combining both high pH and high calcium concentration. We also discuss the function of Sphagnum peat mosses in rendering an alkaline habitat suitable to G. semen growth. Our study highlights that high alkalinity environments act as a major colonization barrier to G. semen . While this finding explains which environmental filters limit G. semen distribution it also helps in understanding its current expansion. With globally decreasing calcium concentrations in freshwater ecosystems, new habitats have and will become conducive to G. semen growth.